Germinação e armazenamento de aquênios de arnica (Lychnophora pinaster Mart.) coletados em diferentes estádios de maturação - Melo, Paulo Régis Bandeira de (2005)
Arnica (Lychnophora pinaster Mart) is from Asteraceae family, with medicinal properties, natural from rocky fields, considered endemic and threatened species. The objective of this work was to contribute with studies referring to seed collection, germination and storage, aiming to guarantee perpetuation through sexual propagation and future domestication of the species for commercial cultivations. The seeds used were collected in December of 2003, in the district of Itumirim, MG, at two maturation stages, based on the morphologic characters of the capitulum, seeds showing internal papus and seeds with absence of internal papus at the time of dispersion. The seeds were dried, cleaning and separated with vertical blower. X-rays machine was used to identify formed, badly formed and empty seeds. The effect of light and five temperatures for germination, as well as storage behavior during six months of storage at different conditions were evaluated. The radiation of 30Kv per 45 seconds allowed the best visualization of the internal structures of the seeds. The maturation stage capitulum with seeds without internal papus at the time of dispersion is the best time for seed collection. The temperature of 20-30oC was the more efficient for seed germination. In relation to light incidence, the seeds showed a tendency of being photoblastic positive, mainly under continuous temperatures. There was no difference regarding the four different storage conditions; arnica seeds may be storage for a period of six months in paper packing or plastic in cold chamber at 10oC/50%RH or room temperature. During storage there was an increase in germination for the unripe seeds, when the internal papus is still attached to the seeds.